2012
DOI: 10.1103/physrevb.86.144109
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic point-defect equilibria in tetragonal ZrO2: Density functional theory analysis with finite-temperature effects

Abstract: We present a density functional theory (DFT) framework taking into account the finite temperature effects to quantitatively understand and predict charged defect equilibria in a metal oxide. Demonstration of this approach was performed on the technologically important tetragonal zirconium oxide, T-ZrO 2 . We showed that phonon free energy and electronic entropy at finite temperatures add a non-negligible contribution to the free energy of formation of the defects. Defect equilibria were conveniently casted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 71 publications
(73 reference statements)
3
64
0
Order By: Relevance
“…The energies of each image were calculated using density functional theory (DFT) with Vienna Ab initio Simulation Package (VASP) [26][27][28][29] with a 2 × 2 × 2 supercell and a 2 × 2 × 2 k-point grid. The generalized gradient approximation (GGA) with a Perdew-Burke-Ernzerhof (PBE) functional [30,31] [24,16,32].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energies of each image were calculated using density functional theory (DFT) with Vienna Ab initio Simulation Package (VASP) [26][27][28][29] with a 2 × 2 × 2 supercell and a 2 × 2 × 2 k-point grid. The generalized gradient approximation (GGA) with a Perdew-Burke-Ernzerhof (PBE) functional [30,31] [24,16,32].…”
Section: Methodsmentioning
confidence: 99%
“…In previous work, by combining first-principles-based pointdefect calculations with statistical thermodynamics, we were able to predict equilibrium defect concentrations at various temperatures and oxygen partial pressures both in tetragonal [24] and monoclinic ZrO 2 [16]. Here we calculated the migration barriers of different oxygen defect types and migration paths by first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%
“…In several cases, hybrid functionals have been shown to outperform other functionals in describing electronic structure and optical properties of materials, and thus, they were assumed to be accurate and superior in all other cases. This opinion was recently disputed by many authors like Youssef and Yildiz 19 and Ramprasad et al 20 who argued that given the known underestimation of formation energies by PBE, hybrid functionals does overestimate them in many cases. Another reason we chose not to use hybrid functionals is that here our focus is not entirely on the absolute values of the formation energies but rather the trends produced by changes in the composition from group III to group V as will be shown in Sec.…”
Section: Methodology a Computational Detailsmentioning
confidence: 99%
“…[39,43,29,5,2,3]), focusing significantly less on the most stable m-ZrO 2 form. Foster et al reported an evaluation of charged and neutral vacancies in the m-ZrO 2 bulk.…”
Section: Introductionmentioning
confidence: 99%